Efforts to accelerate the export of creative craft industries through business intelligence model framework - Munawar, Fansuri; Munawar, Ghifari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This article seeks to develop a framework model for a business intelligence system mapping West Java's exports of creative crafts. The fundamental issue is that the craft industry's exports are underperforming due to a lack of responsiveness in capturing export opportunities. In addition, the lack of a business intelligence system in the craft industry to evaluate export mapping on the global market emphasizes the importance of this research. This body of literature employs the research methods of data gathering and consolidation, determining information needs, and developing a framework for business intelligence. This study investigates primary data regarding the export of handicrafts from West Java, including exporter data, export commodity data (HS code), export trade transactions, export destination country data, and the overall export value and volume. The proposed model is a framework for mapping the export of craft creative industries and the stages of business intelligence (BI) deployment. Based on the results and discussion, the proposed BI framework can serve as a basis for developing a business intelligence system to evaluate the export mapping of handcraft products in West Java.